A prospective and open label study of use of cilnidipine and chlorthalidone fixed dose combination in Indian hypertensive patients, intolerant or uncontrolled on amlodipine and hydrochlorothiazide combination - Sagarad, Suresh V.; S., Hari Prasad (International Journal of Advances in Medicine, 2017)
Background: Primary aim of this study was to evaluate the antihypertensive efficacy of the Cilnidipine and Chlorthalidone fixed dose combination in Indian hypertensive patients who are not controlled on traditionally used amlodipine and hydrochlorothiazide combination and also to evaluate the safety of this combination. Methods: A total of 70 eligible patients were enrolled in this prospective, open label study. The patients were given cilnidipine (10 mg) and chlorthalidone (12.5 mg) who had not achieved target blood pressure (140/90 mmHg) despite on amlodipine (5 mg) and hydrochlorothiazide (12.5mg) combination or are intolerant to the medication. The assessment was done at the end of 4 weeks and 8 weeks. Results: There were significant falls in the SBP (5.43±2.45 mmHg, P<0.05), and DBP (4.11±2.35 mmHg, P<0.05) at the end of 4 weeks as compared to those at the baseline. The trend was sustained at 8 weeks. No further significant fall in the SBP and DBP were noted after 4 weeks (5.43±2.45 and 5.22±2.38 mmHg at 4 weeks vs 4.11±2.35 and 4.01±2.23 mmHg at 8 weeks P=NS). The SBP target (140 mmHg) was achieved in 25 patients (35.71%). The DBP target (90 mmHg) was achieved in 18 patients (25.71%). The combined SBP and DBP target was achieved in 12 patients (17.14%). A similar fall in the SBP was observed in the subgroups which were analysed. Conclusions: The hypertensive patients who do not achieve the target blood pressures on amlodipine and hydrochlorothiazide can be switched to the cilnidipine and chlorthalidone combination. The combination is effective and well tolerated.